MODELING OF GAS TURBINE COOLING SYSTEMS WITH AIR COOLERS - Tarasov, Alexander; Lytvynenko, Oksana; Myhaylova, Irina (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2019)
When cooling gas turbines, an air cooler can be used what presents certain difficulties for the modeling. It is caused by the fact that modern gas turbine cooling system may consist of 1000 or more channels. Modeling of such large systems is successfully performed using the THA (Thermal & Hydraulic Analysis) software package. The method implemented in THA can also be used for air cooler analysis. However, the inserting of the heat exchanger in the general scheme significantly complicates the total scheme. In this regard, it was proposed to represent the heat exchanger with single channel, the properties of which completely determine the different types of heat exchangers. To substantiate this analysis of the operation of a tubular heat exchanger was performed with the help of THA for heat carriers: air-air, air-water, and water-water. It was found that the efficiency of the heat exchanger depends mainly only on the ratio of the mass flow rate heat capacities of the heat-transfer agents. A small scatter of efficiency values relative to the heat exchanger is explained by the dependence of the properties of heat transfer fluid on temperature and pressure. It noted that the coefficient of hydraulic resistance of the heat exchanger as a whole depends on the Reynolds number, wherein the determining the size of an arbitrary diameter can be selected, for example, the diameter of inlet pipe. As a result of such generalizations, a channel of the "heat exchanger" for hydraulic network was created, which absorbed all the main characteristics of the heat exchanger. In conclusion, using THA was carried out comparative calculation of the detailed design of the heat exchanger and the simplified scheme in which the heat exchanger was represented by single channel. A good agreement was obtained between the calculation results, which allow recommending this channel for using in gas turbine cooling systems.